CGIAR Collaborative Platform for Gender Research - Gender meets big data - Tyszler, Marcelo (CGIAR Collaborative Platform on Gender Research, 2019)
Presented by Marcelo Tyszler (CGIAR Collaborative Platform for Gender Research / KIT Royal Tropical Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.